Signal transduction - Kramer, IJsbrand M. (London : Elsevier/Academic Press, 2016)
'A reference on cellular signaling processes, the third edition of Signal Transduction continues in the tradition of previous editions, in providing a historical overview of how the concept of stimulus-response coupling arose in the early twentieth century and shaped our current understanding of the action of hormones, cytokines, neurotransmitters, growth factors and adhesion molecules. In a new chapter, an introduction to signal transduction, the book provides a concise overview of receptor mechanisms, from receptor -ligand interactions to post-translational modifications operational in the process of bringing about cellular changes. The phosphorylation process, from bacteria to men, is discussed in detail. Signal transduction third edition further elaborates on diverse signaling cascades within particular contexts such as muscle contraction, innate and adaptive immunity, glucose metabolism, regulation of appetite, oncogenic transformation and cell fate decision during development or in stem cell niches. The subjects have been enriched with descriptions of the relevant anatomical, histological, physiological or pathological condition.'--Page 4 of cover.
Prologue : signal transduction from an historical perspective -- An introduction to signal transduction -- Regulation of muscle contraction by adrenoceptors -- Cholinergic signaling and muscle contraction -- Sensory signal processing; visual transduction and olfaction -- Intracellular calcium -- Bringing the signal into the nucleus : regulation of gene expression -- Nuclear receptors -- Protein kinase c in oncogenic transformation and cell polarity -- Regulation of cell proliferation by receptor tyrosine protein kinases -- Signal transduction to and from adhesion molecules -- WNT signaling and the regulation of cell adhesion and differentiation -- Activation of the innate immune system : the toll-like receptor-4 and signaling through ubiquitinylation -- Chemokines and traffic of white blood cells -- Activating the adaptive immune system : role of non-receptor tyrosine kinases -- Signaling through the insulin receptor : phosphoinositide 3-kinases and AKT -- TGF[beta] and signaling through receptor serine/threonine protein kinases -- Protein phosphatases -- Cell fate determination by notch.
Includes bibliographical references.
Online resource; title from PDF title page (ScienceDirect, viewed November 4, 2015).
Elsevier
Keywords: Cellular signal transduction; Signal transduction; Transduction du signal cellulaire; SCIENCE -- Life Sciences -- Cell Biology; Cellular signal transduction; Signalen; Electronic books